Multi-proxy dating of holocene maar lakes and pleistocene dry maar sediments in the Eifel, Germany - Sirocko, Frank; Dietrich, Stephan; Veres, Daniel; Grootes, Pieter M.; Schaber-Mohr, Katja; Seelos, Klemens; Nadeau, Marie-Josée; Kromer, Bernd; Rothacker, Leo; Röhner, Marieke; Krbetschek, Matthias; Appleby, Peter; et al. (Quaternary science reviews, 2013)
During the last twelve years the ELSA Project (Eifel Laminated Sediment Archive) at Mainz University has drilled a total of about 52 cores from 27 maar lakes and filled-in maar basins in the Eifel/Germany. Dating has been completed for the Holocene cores using 6 different methods (210Pb and 137Cs activities, palynostratigraphy, event markers, varve counting, 14C). In general, the different methods consistently complement one another within error margins. Event correlation was used for relating typical lithological changes with historically known events such as the two major Holocene flood events at 1342 AD and ca 800 BC. Dating of MIS2-MIS3 core sections is based on greyscale tuning, radiocarbon and OSL dating, magnetostratigraphy and tephrochronology. The lithological changes in the sediment cores demonstrate a sequence of events similar to the North Atlantic rapid climate variability of the Last Glacial Cycle. The warmest of the MIS3 interstadials was GI14, when a forest with abundant spruce covered the Eifel area from 55 to 48 ka BP, i.e. during a time when also other climate archives in Europe suggested very warm conditions. The forest of this “Early Stage 3 warm phase” developed subsequently into a steppe with scattered birch and pine, and finally into a glacial desert at around 25 ka BP. Evidence for Mono Lake and Laschamp geomagnetic excursions is found in two long cores. Several large eruptions during Middle and Late Pleistocene (Ulmener Maar - 11,000 varve years BP, Laacher See - 12,900 varve years BP, Mosenberg volcanoes/Meerfelder Maar 41-45 cal ka BP, Dümpel Maar 116 ka BP, Glees Maar - 151 ka BP) produced distinct ash-layers crucial for inter-core and inter-site correlations. The oldest investigated maar of the Eifel is 40Ar/39Ar dated to the time older than 520 ka BP.